Multimorbidity in patients with acute heart failure across world regions and country income levels (REPORT-HF): a prospective, multicentre, global cohort study - Gerhardt, Teresa; Gerhardt, Louisa M. S.; Ouwerkerk, Wouter; Roth, Gregory A; Dickstein, Kenneth; Collins, Sean P; Cleland, John G F; Dahlstrom, Ulf; Tay, Wan Ting; Ertl, Georg; Hassanein, Mahmoud; Perrone, Sergio V; et al. (The lancet. Global health, 2023)
Background - Multimorbidity (two or more comorbidities) is common among patients with acute heart failure, but comprehensive global information on its prevalence and clinical consequences across different world regions and income levels is scarce. This study aimed to investigate the prevalence of multimorbidity and its effect on pharmacotherapy and prognosis in participants of the REPORT-HF study. - Methods - REPORT-HF was a prospective, multicentre, global cohort study that enrolled adults (aged ≥18 years) admitted to hospital with a primary diagnosis of acute heart failure from 358 hospitals in 44 countries on six continents. Patients who currently or recently participated in a clinical treatment trial were excluded. Follow-up data were collected at 1-year post-discharge. The primary outcome was 1-year post-discharge mortality. All patients in the REPORT-HF cohort with full data on comorbidities were eligible for the present study. We stratified patients according to the number of comorbidities, and countries by world region and country income level. We used one-way ANOVA, χ2 test, or Mann-Whitney U test for comparisons between groups, as applicable, and Cox regression to analyse the association between multimorbidity and 1-year mortality. - Findings - Between July 23, 2014, and March 24, 2017, 18 553 patients were included in the REPORT-HF study. Of these, 18 528 patients had full data on comorbidities, of whom 11 360 (61%) were men and 7168 (39%) were women. Prevalence rates of multimorbidity were lowest in southeast Asia (72%) and highest in North America (92%). Fewer patients from lower-middle-income countries had multimorbidity than patients from high-income countries (73% vs 85%, p<0·0001). With increasing comorbidity burden, patients received fewer guideline-directed heart failure medications, yet more drugs potentially causing or worsening heart failure. Having more comorbidities was associated with worse outcomes: 1-year mortality increased from 13% (no comorbidities) to 26% (five or more comorbidities). This finding was independent of common baseline risk factors, including age and sex. The population-attributable fraction of multimorbidity for mortality was higher in high-income countries than in upper-middle-income or lower-middle-income countries (for patients with five or more comorbidities: 61% vs 27% and 31%, respectively). - Interpretation - Multimorbidity is highly prevalent among patients with acute heart failure across world regions, especially in high-income countries, and is associated with higher mortality, less prescription of guideline-directed heart failure pharmacotherapy, and increased use of potentially harmful medications. - Funding - Novartis Pharma. - Translations - For the Arabic, French, German, Hindi, Mandarin, Russian and Spanish translations of the abstract see Supplementary Materials section.
Online verfügbar: 14. November 2023
Gesehen am 09.04.2024